An Architectural Element: Mashrabiya - Demet Taşkan; Alzahraa Behzad Ismaeel (Art-Sanat)
Certain terms of Arabic and Persian origin employed in Islamic art and architecture are used with different meanings in Turkish. “Mashrabiya” is one of those terms. While mashrabiya originated from and was applied in Islamic geography and is the name of an architectural element, it is rather known as a kind of woodworking technique in Turkish Art History literature. This technique is called hart (خرط) in Arabic. The Turkish equivalence of the Arabic word hart is torna. In English, this technique is called lathe. Mashrabiya, on the other hand, is known as an architectural element in all Western sources and has several different definitions. None of those definitions refers to a woodworking technique. This study aims to offer detailed information about the origin and characteristics of mashrabiya, an architectural element, as well as its place in Islamic art, the period when it made its way into the Art History literature and its use and development in Islamic art. The study also aims to contribute to the art history literature by providing information on the hart technique, which has lotsof applied examples in the Turkish art despite not being referred to in our literature as a word, and by offering a Turkish contribution to this technique, which has been named the mashrabiya technique in our literature.